The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 25th International Conference on World Wide Web 2016
DOI: 10.1145/2872427.2883001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Limits to Prediction in Complex Social Systems

Abstract: How predictable is success in complex social systems? In spite of a recent profusion of prediction studies that exploit online social and information network data, this question remains unanswered, in part because it has not been adequately specified. In this paper we attempt to clarify the question by presenting a simple stylized model of success that attributes prediction error to one of two generic sources: insufficiency of available data and/or models on the one hand; and inherent unpredictability of compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 43 publications
3
99
1
1
Order By: Relevance
“…The reason for this incoherence is that prediction results depend on many of the same "researcher degrees of freedom" that lead to false positives in traditional hypothesis testing (3). For example, consider the question of predicting the size of online diffusion "cascades" to understand how information spreads through social networks, a topic of considerable recent interest (6,7,10,11). Although seemingly unambiguous, this question can be answered only after it has first been translated into a specific computational task, which in turn requires the researcher to make a series of subjective choices, including the selection of the task, data set, model, and performance metric.…”
Section: Standards For Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this incoherence is that prediction results depend on many of the same "researcher degrees of freedom" that lead to false positives in traditional hypothesis testing (3). For example, consider the question of predicting the size of online diffusion "cascades" to understand how information spreads through social networks, a topic of considerable recent interest (6,7,10,11). Although seemingly unambiguous, this question can be answered only after it has first been translated into a specific computational task, which in turn requires the researcher to make a series of subjective choices, including the selection of the task, data set, model, and performance metric.…”
Section: Standards For Predictionmentioning
confidence: 99%
“…In addition to holding the data set fixed, for simplicity, we also restricted our analysis to a single choice of model, reported in (11), that predicts cascade size as a linear function of the average past performance of the "seed" individual (i.e., the one who initiated the cascade). Even with the data source and model held fixed, Fig.…”
Section: Standards For Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Martin et al [15] showed that realistic bounds on predicting outcomes in social systems imposes drastic limits on what the best performing models can deliver. And yet, accurate prediction is a holy grail avidly sought in nancial markets [8], sports [7], arts and entertainment award events [13], and politics [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to Blastland and Dilnot [1], the teams favored by bettors win half the time in soccer, 60% of the time in baseball, and 70% of the time in football and in basketball. Despite the large amount of money involved, there are no algorithms capable of producing accurate predictions and there is some evidence they will never be found [15].…”
Section: Introductionmentioning
confidence: 99%